Representation of Tenun Gringsing in Indonesian and Japanese Cultural Diplomacy - Ni Luh Putu Cintya Devi; Putu Ratih Kumala Dewi; Ni Wayan Rainy Priadarsini (Andalas Institute of International Studies UNAND, 2024)
This study aims to describe the use of Tenun Gringsing as a medium of Indonesian cultural diplomacy in Japan and to describe the representation of friendship between Indonesia and Japan through the use of Tenun Gringsing. Tenun Gringsing originating from Tenganan Village, Pegringsingan, Karangasem Regency, Bali is a woven fabric with double tie technique which is currently classified as rare and there are only three types of similar fabrics in the world, two of which come from Indonesia and Japan. Tenun Gringsing has received significant attention from general public and fashion designer who integrate apply Gringsing motifs in their designs as well as at international cultural exchange events. Tenun Gringsing involvement in cultural activities, one of which is carried out in Japan, the existence of Tenun Gringsing further strengthens its position as an effective instrument of cultural diplomacy in strengthening friendly relations between Indonesia and Japan. The result of the study shows that Tenun Gringsing not only functions as a traditional art product, but also as a symbolic of Indonesian cultural identity introduces through various cultural diplomacy activities, such as cultural festivals and workshops in Japan.